Effect of microfine barytes filler on flyash and flyash lime gypsum concretes subjected to elevated temperatures - Narayana, S.M.V.; Swamy, N. Kumara (Journal of Structural Engineering, 2025)
Accidental fires quite often occur in domestic buildings, function halls, commercial complexes, industries, furnaces etc. During fire accidents, concrete is subjected to elevated temperatures and after the fire is extinguished by water, it undergoes immediate cooling effect. To endure all these effects, the concrete must be resistant to elevated temperatures. Conventional OPC concrete is not so effective in resisting elevated temperatures. To improve further the temperature resistance of flyash concrete, in the present investigation, microfine heavy weight inert filler is added to flyash concrete and the residual compressive strength of concrete at elevated temperatures ranging from 100°C to 300°C has been studied. The flyash concrete with microfine barytes filler shows more resistance to elevated temperature at all temperatures and duration of temperatures in hot, immediately water cooled and air cooled conditions.